2022
DOI: 10.1111/jfpp.17120
|View full text |Cite
|
Sign up to set email alerts
|

The optimization of plasma activated water ( PAW ) generation and the inactivation mechanism of PAW on Escherichia coli

Abstract: Plasma activated water (PAW) generated by nonthermal plasma, an acidified solution containing a variety of reactive species, has become a new decontamination approach because of its bactericidal ability. This study investigated the effects of various generation conditions of PAW on bactericidal activities against Escherichia coli and its physicochemical properties. PAW was prepared by ultrapure water with dielectric barrier discharge (DBD) plasma. The optimal generation condition of PAW was 30 min plasma activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…However, few researchers have proposed that the ROS in PAW are also responsible for the microbial inactivation of PAW by initiating lipid peroxidation in the cell membrane (Gan et al, 2022;Perinban et al, 2022). Han et al (2022) reported that •O 2 − has a key role in the mechanism of antimicrobial inactivation induced by PAW while NO − 2 and NO − 3 with pH drop acted as the supporting agents in the inactivation. •OH also plays a role in the bacterial inactivation by oxidizing unsaturated fatty acids in the cell membrane, cleaving peptide bonds, and oxidizing amino acid side chains (Guo et al, 2023).…”
Section: Microbial Inactivation By Pawmentioning
confidence: 99%
See 3 more Smart Citations
“…However, few researchers have proposed that the ROS in PAW are also responsible for the microbial inactivation of PAW by initiating lipid peroxidation in the cell membrane (Gan et al, 2022;Perinban et al, 2022). Han et al (2022) reported that •O 2 − has a key role in the mechanism of antimicrobial inactivation induced by PAW while NO − 2 and NO − 3 with pH drop acted as the supporting agents in the inactivation. •OH also plays a role in the bacterial inactivation by oxidizing unsaturated fatty acids in the cell membrane, cleaving peptide bonds, and oxidizing amino acid side chains (Guo et al, 2023).…”
Section: Microbial Inactivation By Pawmentioning
confidence: 99%
“…In addition, the storage temperature of 4 • C maintained the inactivation efficacy of PAW higher than at 22 • C (Wang & Salvi, 2021). Han et al (2022) evaluated the influence of storage times at 7.5, 15, 30, and 60 min at room temperature during the PAW inactivation efficacy against planktonic E. coli. The authors reported that more than 6.18 log 10 reduction CFU.mL −1 of PAW was achieved with the storage time of 7.5 min (Figure 7).…”
Section: 21mentioning
confidence: 99%
See 2 more Smart Citations